1999
DOI: 10.1017/s0029665199001093
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of food choice

Abstract: fax +44 (0)1483 259553, email R. Shepherd@surrey.ac.uk Food choice is influenced by a large number of factors, including social and cultural factors. One method for trying to understand the impact of these factors is through the study of attitudes. Research is described which utilizes social psychological attitude models of attitude-behaviour relationships, in particular the Theory of Planned Behaviour. This approach has shown good prediction of behaviour, but there are a number of possible extensions to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
153
2
20

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(187 citation statements)
references
References 31 publications
4
153
2
20
Order By: Relevance
“…There is a relationship between television food advertisements recalled by children and their consumption of these foods 57 . Food choice is the result of an interaction between many factors 58 but, as Inchley et al 13 point out, a number of health promotion initiatives have shown signs of success in improving the diets of young people. There is undoubtedly need for continuing and coordinated effort if consumption, and the frequency of consumption, of NMES is to be reduced.…”
mentioning
confidence: 99%
“…There is a relationship between television food advertisements recalled by children and their consumption of these foods 57 . Food choice is the result of an interaction between many factors 58 but, as Inchley et al 13 point out, a number of health promotion initiatives have shown signs of success in improving the diets of young people. There is undoubtedly need for continuing and coordinated effort if consumption, and the frequency of consumption, of NMES is to be reduced.…”
mentioning
confidence: 99%
“…social setting) and aspects of the person (e.g. food identity) may be more influential (Axelson & Brinberg, 1992;Bisogni, Connors, Devine & Sobal, 2002;Booth, 1994;Meiselman & MacFie, 1996;Shepherd, 1999). The findings presented here suggest that people differentially weight these considerations by the categories they use to classify foods.…”
Section: Discussionmentioning
confidence: 68%
“…Other studies have also reported the tendency for non-diagnosed persons to underestimate their risk of CVD 27,33,34 , unless there is an awareness of a prior family history 35 . Likewise, we found that awareness of one's genetic predisposition to heart disease appeared to motivate some people to engage in dietary and lifestyle modification, while discouraging those with more fatalistic views.…”
Section: Registered Dietitiansmentioning
confidence: 99%